Albania : Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Review Under the Extended Arrangement, and Financing Assurances Review; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Albania. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
The staff report for Albania's Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility is presented. The economy has achieved robust noninflationary growth, albeit with increasing external imbalances, and has begun to tackle longstanding problems in the business environment. The upcoming elections risk diverting policymakers' attention from stability-oriented policies. Despite significant buffers and inbuilt strengths of the financial sector, continued diligent supervision, high-frequency monitoring, and enhanced cooperation with foreign supervisors of resident banks will be needed to underpin prompt, proactive responses to changing circumstances.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet